Prevalence and correlates of current cigarette smoking among transgender women in Argentina - Cartujano-Barrera, Francisco; Mejia, Raul M.; Radusky, Pablo D.; Cardozo, Nadir; Duarte, Mariana; Fabian, Solange; Caballero, Romina; Zalazar, Virginia; Ramos-Pibernus, Alixida; Alpert, Ash B.; Cupertino, Ana Paula; Frola, Claudia; et al. (Frontiers in Public Health, 2023)
Objective To assess the prevalence of current cigarette smoking among transgender women in Argentina, and to examine the unique associations of current cigarette smoking with demographic and psychosocial factors. Methods This study is a secondary data analysis of the TransCITAR – a prospective cohort study of transgender individuals living in Buenos Aires, Argentina – baseline data. The baseline survey collected information on sociodemographic characteristics, perceived health status, depressive symptoms, suicide attempts, current cigarette smoking, alcohol use disorder, and substance use. Participants were also asked about lifetime experiences of physical and sexual violence perpetrated by partners, clients and/or the police, and experiences of gender identity stigma in the past year from healthcare workers and the police. Lastly, participants were asked if they had ever been arrested. Fisher’s exact test was used to compare proportions in categorical variables and student t-test was used for continuous variables. Significant associations with current cigarette smoking were tested in a logistic regression model adjusted for all significant associations. Results A total of 41.7% of participants (n = 393) reported current cigarette smoking. Compared to their non-smoking counterparts, participants who reported current cigarette smoking (1) had completed less education, (2) were more likely to be born in Argentina, (3) more likely to had migrated to Buenos Aires from other parts of the country, (4) more likely to report a history of sex work, (5) more likely to perceive their health as excellent, (6) more likely to screen positive for hazardous alcohol drinking, (7) more likely to report any substance and cocaine use in the past year, (8) more likely to experience gender identity stigma from the police in the past year, and (9) more likely to being arrested in their lifetime (all p’s < 0.05). After controlling for all significant associations, education level of less than high school (AOR = 1.79, 95% CI 1.02–2.12), hazardous drinking (AOR = 2.65, 95% CI 1.30–5.37), and any substance use in the last year (AOR = 2.14, 95% CI 1.16–3.94) were positively and independently associated with current cigarette smoking. Conclusion Among transgender women in Argentina, current cigarette smoking was more than double the rate for cisgender women. Current cigarette smoking was associated with education, hazardous drinking, and any drug use. These results will inform future smoking cessation interventions among transgender women in Argentina.